Pendampingan Pengrajin Batik Berbasis Ekonomi Sirkular Melalui Olahan Limbah Tekstil Batik Sebagai Wujud Implementasi Kebijakan Industri Hijau - Sutarjo, Sutarjo; Lailatul Fitria, Nurul Jannah; Wijayanti, Awit; Elawati, Elawati; Fitriana, Pipit; Napipah, Pipih (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to improve the understanding, skills, and environmental awareness of batik artisans in Probolinggo City through the processing of batik textile waste based on a circular economy as an implementation of green industry policies. The method applied in this program employed a participatory approach or Participatory Action Research (PAR). The partners involved were 10 batik artisans and batik fashion tailors in Probolinggo City. Data collection instruments included questionnaires, interviews, and direct observations, which were analyzed descriptively. The results of the program indicated an increase in the partners’ understanding and skills related to the knowledge and techniques of managing batik textile waste within a circular economy system as part of green industry practices. In addition, the partners experienced improved income and heightened awareness in managing batik textile waste into products with significant functional, historical, and economic value. The batik artisans also demonstrated strong environmental concern and enhanced commitment toward green industry branding.